POLICY IMPLEMENTATION OF REGULATION NUMBER 21 OF 2020 CONCERNING LARGE-SCALE SOCIAL RESTRICTIONS (PSBB) IN THE FRAMEWORK OF ACCELERATION OF THE HANDLING OF COVID-19 IN TANETE RIAJA SUB-DISTRICT, BARRU REGENCY - Mukmin Muhammad (Sean Institute, 2023)
The results of this study indicate that PERDA No. 21 of 2020 concerning PSBB in Tanete Riaja Subdistrict, Barru Regency is not enforced when we comply with health protocols such as: Not leaving the house, washing hands, maintaining distance, not having direct contact, avoiding public transportation, and limiting direct contact with pets. TaneteRiaja District's efforts to dealing with this, follow the government's recommendations that have been set, and guard every border so that no foreigners enter the Tanete Riaja District environment.